Allergic Reactions to Drugs in Children - Rajabturdiyevna, Yomgurova Ozoda (Journal of Science in Medicine and Life, 2024)
Drug allergies are characterized by the occurrence of hypersensitive reactions to medications that have an immune mechanism of development. In such reactions, antibodies and/or activated T cells are directed against drugs or their metabolites. This problem is very relevant for practical healthcare, since more than 7% of the population suffers from drug allergies.